Improving community understanding of cascading effects of critical infrastructure service failure: An experimental interactive learning process - Deepshikha Purwar; Johannes Flacke; Richard Sliuzas (Progress in Disaster Science)
Effective disaster preparedness relies on the community's understanding of hazards and risks, emphasizing the need to address cascading effects from critical infrastructure failures due to natural hazards. Understanding cascading effects in communities facing multiple hazards is crucial due to the increasing complexity of critical infrastructure (CI) services. Limited awareness can amplify vulnerabilities and socioeconomic losses, and thus capacity building at the community level is essential for reducing hazard risks. This study utilized an interactive learning process (ILP), a participatory approach to engage the community in sharing experiences and building coping capacity for cascading effects. ILP was facilitated through facilitator-learner interaction and participatory exercises, aided by visualisation tools that enriched the learning experience of participants. The use of visualisation tools in ILP simplified comprehension of intricate interdependencies, helping participants to brainstorm and think critically to explore potential solutions. We explore the effectiveness of three visualisation tools that support the ILPs in improving community understanding of the cascading effects. Through experimentation and comparison, insights are gained into how learners engage with different ILPs and their impact on overall learning outcomes. The study concluded by selecting the visualisation tool supporting ILP that was effective in fostering engagement, improving understanding, and promoting knowledge retention.